Relações entre o tipo psicológico e a aprendizagem de uma língua estrangeira - Belonsi, Lileni Marileili Drugovich (2009)
There are several factors which interfere in foreign language learning. Among them, there are the learning styles, which comprise the cognitive and affective domains. The intrinsic side of the affective domain, which is the personality, should be considered as an important factor on the building of a foreign language teaching/learning theory, because it gives priority to human behavior concerning the way people learn. Although Personality Traits or Psychological Types may be regarded as circumstantial, that is, without reliability or strength, they may be indicators of personal needs during a certain moment. The purpose of this study was to investigate whether the learner s Psychological Type is reflected on the way he processes information, on his motivation and on the way he develops strategies which help him to deal with the most different learning situations. Knowing the different Psychological Types (such as extroverted, perceptive, judger, intuitive) as well as their characteristics, may be quite important for the teacher, because, through this knowledge, he will be able to better identify the difficulties of a determined learner or a group of learners and provide them with means to reduce them; in relation to the learner, one will have conditions to search more autonomy when learning a foreign language, because one will know how to satisfy his preferences and how to deal with his learning difficulties. By having as theoretical base the studies developed by the psychiatrist Carl Jung in the 1920s, which were further revised and improved by Myers and Briggs (1987; 1995; 1997) and having as reference the studies developed by Ehrman (1996), we pointed out some personality differences which are relevant to the learning process. We analyzed and interpreted the data, which were collected from the answers given at the MBTI (Myers Briggs Type Indicator). The MBTI is an inventory developed by Myers and Briggs, which indicates the Psychological Type, classified into four bipolar or dichotomic dimensions according to the learner s preferences. Such data showed the traits of each Type, the relationship between the orientations and the abilities of each learner and the factors which contribute or not to the success in a foreign language (English) learning context.